2022
DOI: 10.1088/2515-7620/ac66ca
|View full text |Cite
|
Sign up to set email alerts
|

Responses of vegetation growth to climate change over the Tibetan Plateau from 1982 to 2018

Abstract: The Tibetan Plateau (TP) plays a critical role in Earth’s climate system and is highly sensitive to global warming. However, comprehensive analysis of the interaction between various climatic factors and vegetation growth across the TP is still limited. Using daily NDVI series interpolated from the 16-day satellite measurements and climatic data during 1982-2018, we investigated the spatiotemporal changes in growing season NDVI (NDVIGS) and associated climatic drivers over the TP and analyzed the responses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…These findings align with the negative trends in the aridity index affecting natural vegetation in the upper reaches of the Shiyang River Basin, as illustrated in Figure 8. Similar patterns have been observed in previous studies that explore ecosystem vulnerability to climate change in the Tibet plateau [113][114][115]. Furthermore, the research highlights the impact of temperature and evaporation gradients, coupled with a decrease in rainfall, on the gradual decline in vegetation cover from upstream to the lower reaches.…”
Section: Discussionsupporting
confidence: 85%
“…These findings align with the negative trends in the aridity index affecting natural vegetation in the upper reaches of the Shiyang River Basin, as illustrated in Figure 8. Similar patterns have been observed in previous studies that explore ecosystem vulnerability to climate change in the Tibet plateau [113][114][115]. Furthermore, the research highlights the impact of temperature and evaporation gradients, coupled with a decrease in rainfall, on the gradual decline in vegetation cover from upstream to the lower reaches.…”
Section: Discussionsupporting
confidence: 85%
“…Other factors, such as changes in cloud cover, solar radiation, and vegetation growth activity, may also contribute to this decrease in diurnal temperature range, and these factors also warrant further investigation in the future. Moreover, in addition to temperature, precipitation, wind speed, humidity, and snowmelt also have an impact on vegetation dynamics [21,68], although the mechanisms underlying the joint influence of air temperature and these other factors on vegetation growth are not yet fully understood. Given the spatial heterogeneity of climatic conditions, it is crucial to conduct comprehensive attribution analyses that link spatiotemporal changes in vegetation growth on the TP with multiple climatic variables.…”
Section: Possible Uncertainty Sources and Future Workmentioning
confidence: 99%
“…The latest study has indicated that the annual marsh net primary productivity (NPP) on the TP significantly increased with the rising minimum temperatures during winter and spring [20]. However, there is limited research that compares the impact of diurnal and nocturnal warming on vegetation growth across the TP [21]. Considering the asymmetric rise in daytime and nighttime temperatures worldwide, it is imperative to investigate how changes in these temperatures can impact plant growth on the TP, especially on different types of frozen soils.…”
Section: Introductionmentioning
confidence: 99%